P044 Giant cell arteritis in an immunocompromised patient with rheumatoid arthritis. (23rd April 2022) - Chauhan, Neal; Kinder, Alison
Abstract: Background/Aims: Giant cell arteritis (GCA) is a common medium-large vessel vasculitis with an approximate incidence of 10 cases per 100, 000 people over 50 years old. First line management of GCA is with high dose glucocorticoids followed by steroid sparing agents, namely methotrexate with tocilizumab for resistant cases. Here we describe a patient established on methotrexate for rheumatoid arthritis, receiving rituximab with intravenous methylprednisolone (IVMP) who went on to develop GCA. Methods: A 65-year-old Caucasian female with seropositive rheumatoid arthritis (RA) established on 20mg weekly subcutaneous methotrexate and low dose 5mg prednisolone was escalated to her tenth cycle of rituximab with 100mg IVMP for an arthritic flare. The day after her second infusion, two weeks apart, the patient presented with headaches. These were severe temporal pains with scalp tenderness for the past four weeks. She denied visual changes, jaw claudication or polymyalgia rheumatica features. Examination identified bilateral thickened and tender temporal arteries. Ultrasound confirmed bilateral frontal temporal artery halo signs, with intimal thickening of 0.9mm and 0.4mm of the left and right respectively. Blood tests showed a rise in C-reactive protein to 46mg/L from 13mg/L. In view of these findings, procedural risks and recent immunosuppression biopsy was not sought. The patient was commenced on 40mg prednisolone before weaning by 5 mg 2-3 weekly. Her headache improved, without relapse and her CRP normalised within 2 weeks. Given tocilizumab had previously been ineffective in the patient's RA management, she declined transition to this biologic and her methotrexate was increased to 25mg. Results: Development of GCA in a patient with pre-established immunotherapy is rare. This report represents only the second case noted in the literature of the vasculitis occurring in a patient whilst on rituximab. Excluding tocilizumab (anti-IL6), a meta-analysis of other biological agents including infliximab, adalimumab, etanercept (anti-TNF) and abatacept (anti-CTLA4) have not been proven to have clinical significance over placebo in GCA. However, evidence of rituximab and its role in GCA is limited with no clinical trials. Contrary to this case of GCA, rituximab (anti-CD20) therapy has a well-recognised role in ANCA associated vasculitis and there are growing calls for trials in large vessel vasculitides. Recent case series of rituximab in Takayasu's arteritis have presented contrasting outcomes of persistent disease activity versus clinical and laboratory remission. Robust clinical trials are therefore required to evaluate the long-term impact of rituximab on large vessel vasculitis. Conclusion: Although rare, clinicians should be vigilant for the development of GCA despite established immunosuppression. Disclosure: N. Chauhan: None. A. Kinder: None.